Amalan penyeliaan penyelidikan pelajar Pasca Ijazah di Universiti Teknologi Malaysia - Muhammad, Nur Atikah (2010)
Supervision of research is an academic activity that is designed and implemented to enhance learning and maximize the learning experience of students at postgraduate level. Research supervision practices have a close relationship with the factors that influence the supervisory process. What sort of research supervision being practiced at the Universiti Teknologi Malaysia (UTM)? This study aimed to evaluate supervisory practices in research among students pursuing postgraduate studies at UTM and supervisory practices to identify the impact on the quality of research undertaken. Therefore, this study involves eleven principles and practices of supervision of eleven factors that affect supervision. Among other factors such factor is the administration and the work environment, culture, research, resources and facilities, the selection of topics and programs, communication and involvement in research, mentoring students, interpersonal communication between supervisors and students, feedback from supervisors, supervisory skills, writing thesis and professional development. The study was conducted using a questionnaire modified from the Evaluation of Postgraduate Supervision (SEPS), which is produced by the Queensland University of Technology. Data analyzed use Statistical Packages for Social Sciences (SPSS) and retrieval are reported in descriptive statistics form and inference. The findings revealed that students less involved with the activities of the department and the faculty did not provide adequate resources and facilities to students. However, most students agreed that the supervisor is wise to evaluate and monitor the final project and final presentation of the research. Factors and relationships between supervisors and student participation were also at the highest level. In addition, the T-test and ANOVA analysis conducted on six categories of demographics, it was found that there were only two demographic categories that have the most significant differences in supervisory principles and practices of supervision of the factors that influence the type of gender and faculty.